On the taxonomy of Philyra sagittifera (Alcock, 1896) and P. concinnus Ghani & Tirmizi, 1995 (Decapoda, Brachyura, Leucosiidae), with description of a new genus from the Indian Ocean - Patel, Krupal; Naderloo, Reza; Trivedi, Jigneshkumar; Mitra, Santanu (Zootaxa, 2023)
The identity of the leucosiid crabs, Philyra sagittifera (Alcock, 1896) and P. concinnus Ghani & Tirmizi, 1995, originally described from Pakistan is clarified. Redescription of the lectotype male of Philyra sagittifera (Alcock, 1896) and fresh material of both species collected from the Persian Gulf revealed that these two species show significant morphological differences from the generic characters of Philyra sensu stricto and other allied genera in possessing three broad tuberculated ridges united to form a "broad-arrow" pointing forwards on the carapace, and male G1 with apical process curved, with or without a spatulate tip. Therefore, a new genus Tirmilyra n. gen. is established to accommodate both species.